The Integration of Artificial Intelligence in Teaching Language and Grammar to Arabic Language Students: A Field Study on the Impact of Modern Technologies on Language Skills Development - Amayreh , Muhammad Ismail; ALrawagfeh, Omar; Amer, Amal . (Dirasat: Human and Social Sciences, 2026)
Objectives: This study aims to explore role of artificial intelligence (AI) in enhancing education of Arabic language department students in universities. It focuses on analyzing benefits and challenges associated with using technologies. Additionally, it examines the impact of AI on improving students' efficiency, enhancing the quality of their learning, achieving educational goals faster and more accurately, and identifying the gap between current state of AI integration in education and future opportunities. Methodology: research utilized a designed field survey distributed to a sample of 216 students from Arabic Language Department at Philadelphia University in Jordan. The survey included questions covering aspects of AI usage, such as knowledge acquisition, academic performance improvement, and assignment completion. It also assessed students' perceptions of AI's influence on efficiency and learning capabilities. Results: findings revealed that AI is a valuable addition to university education. Most students perceived it as a tool that saves time and effort while enhancing academic performance quality. However, the study highlighted challenges related to the quality of AI outputs in Arabic, insufficient training in utilizing these technologies, and over-reliance on AI, which may negatively impact the development of critical and creative thinking skills. Conclusion: study emphasizes importance of AI as promising educational tool. It also underscores the need to develop tools and technologies better suited to specific characteristics of Arabic language. Furthermore, it highlights importance of raising academic awareness about optimal use of tools to improve the quality of education while minimizing associated risks.